PENGARUH PEMBERIAN EDUKASI BANTUAN HIDUP DASAR TERHADAP PERILAKU MASYARAKAT NELAYAN DALAM PENYELAMATAN KORBAN TENGGELAM DI PESISIR PANTAI DESA LISABATA KECAMATAN TANIWEL - Bugis, Dewi Arwini; Rani An, Desi (STIKES Pasapua Ambon, 2022)
Introduction: The majority of Indonesia’s population live in coastal areas whose main livelihood is as fishermen. The biggest risk for people living in coastal areas is the problem of drowning accidents. One way to minimize the number of victims who die from drowning in the waters is to get Basic Life Assistance (BHD) first aid provided by every community member who was near the victim when the drowning occurred. Methods: This study used a pre-experimental design with a one group pretest-posttest approach. The population and sample in this study were all fishing communities living on the coast of Lisabata Village, Taniwel District, totaling 43 people using the Total Sampling technique. The data analysis uses the Wilcoxon Test.. Results: Research that has been conducted on 43 respondents with test results using the Wilcoxon test shows a significant value of 0.000. Because the value is 0.000 <0.05, it can be concluded that Ha is accepted and H0 is rejected, which means that there is an effect of providing basic life support education on the behavior of fishermen in saving drowning victims on the coast of Lisabata Village, Taniwel District. Conclusion: There is an effect of providing Basic Life Support education on the behavior of the fishermen community in rescuing drowning victims on the coast of Lisabata Village, Taniwel District.Suggestion: It is hoped that fishermen can learn more about how to provide Basic Life Assistance in saving drowning victims from information media or social media to further deepen their knowledge, attitudes and correct actions before carrying out rescue actions.